Wandering stars [book club bag] - Orange, Tommy, 1982- (Alfred A. Knopf, 2024)
"Wandering Stars traces the legacies of the Sand Creek Massacre of 1864 and the Carlisle Industrial School for Indians through to the shattering aftermath of Orvil Redfeather's shooting in There There"--